Studi Kompressibilitas Tanah Vulkanik yang Dipadatkan Dengan Cara Statik dan Dinamik - Gagas Prabowo; Paulus Pramono Rahardjo; Rinda Karlinasari (Universitas Islam 45, 2023)
Road construction projects in Indonesia are often located on volcanic soils, where borrow pit options will be limited to volcanic soils. In the construction of compacted earth roads generally have an immediate settlement, but in fact there is a long-term settlement in compacted soil. In general, the compaction carried out in the field is different from that in the laboratory. Where compaction in the field leads to static conditions while in the laboratory it is dynamic. This study aims to analyze the mechanism of static or dynamic compaction and its relationship with compressibility. Determination of creep using Oedometer testing with saturation and unsaturated methods. Laboratory test results show that different compaction methods will affect the dry unit weight value of the soil, where in this test the dry unit weight value for dynamic compaction is 1,38 g/cm3 and for static compaction it is 1,44 g/cm3 or an increase of 4,35% to 7,96% . The value of the secondary consolidation coefficient increases along with increasing load on the Oedometer test, but with different characteristics for each sample. In this study, the secondary consolidation coefficient tends to decrease by 10% – 40% when using higher compaction energy. While the compressibility index value decreased to 52%.